Miss Emily - Mutén, Burleigh (Candlewick Press, 2014)
"When an invitation to join Miss Emily in the garden appears, Mattie, Ned, Sally, and Mac know they're in for some fun because Miss Emily...Emily Dickinson to the rest of us...always has a surprise in store for her young friends. And today's may be the biggest adventure yet. Mac, the youngest member of the group, tells what happens when a reclusive poet and her band of pretend Gypsies wait for the midnight circus train to arrive."...Jkt. flap